P1021Low incidence of atrial tachycardia following ablation of low voltage areas in sinus rhythm for persistent atrial fibrillation. (18th June 2020) - Lepillier, A; Copie, X; Escande, W; Niro, M; Paziaud, O; Piot, O
Abstract: . Background: Dedicated ablation strategies for persistent atrial fibrillation (AF) have shown a limited success rate with frequent atrial tachycardia (AT) occurrence. Recent studies suggest that atrial arrhythmogenic sites are related to tissular heterogeneities and increased fibrosis can be identified as reduced bipolar voltage areas. . Purpose: Targeting low voltage areas (LVA) in addition to PVI may represent an efficient strategy for the ablation of persistent AF, and may limit the risk of AT recurrence. . Methods: We prospectively included consecutive patients with symptomatic persistent AF. The ablation strategy consisted of the following steps: circumferential pulmonary vein isolation (CPVI), Sinus rhythm restoration by electrical cardioversion, voltage map performed in sinus rhythm. Complementary RFA was guided by low voltage areas (0.2-0.4 mV). Success was defined as freedom from AF/ atrial flutter or atrial arrhythmia at 12 months or more. . Results: 101 patients (mean age: 62.5 +/- 10.4 years, men 73%) were included with persistent AF or long standing AF (7%). Procedure time was: 154 ± 25 min and fluoroscopy time: 184 ± 90 sec. Time of RFA was 44.7 +/- 12 min. Mean LA volume was 182 +/- 38 mL. LVA were found in 50 patients (49.5%). The distribution of these areas was: 30 anterior wall 29.7%), 21 septum (20.7%), 19 roof (18.8%), 5 inferior (4.9%), 11 left appendage (10.8%), 6 posterior (5.9%), 3 mitral isthmus (3%). RF ablation was realized for all LVA and homogenisation was attempt. After a single procedure at a mean FU of 12 months, 72.3% of patients were free of symptomatic AF. 27 patients had recurrence of atrial AF: 7 permanent, 15 persistent and 5 paroxysmal AF. Predictive factors of recurrence of AF were: long standing persistent AF, large left atrial volume (> 205 mL), shorts AF cycle length (< 168 ms) and reduce LEVF (< 45%). Atrial tachycardia occurred in 5 patients (4, 9%). Mechanisms of AT were: typical cavo-tricuspid flutter in one patient, peri-mitral flutter in 2 patients, and atrial focal tachycardia (close to pulmonary veins) in 2 patients. . Conclusion: These results suggest that PVI with complementary RF ablation guided on low voltage areas is an efficient strategy for symptomatic persistent AF, and reduce the recurrence of AT following this ablation strategy.